Attention mediates restrained eaters' food consumption intentions. (March 2022) - Moore, Kelly; Walker, Doug; Laczniak, Russ
Highlights: Conclusive results are not evident on the effectiveness of menu calorie labels. Restrained eaters pay more attention to menu calorie labels. Restrained eaters select fewer calorie foods with menu calorie labels present. Eye tracking is useful in gauging consumers' attention to menu calorie labels. The US Affordable Care Act menu calorie labeling provision may help restrained eaters. Abstract: Restrained eaters are chronic dieters who pay attention to their food choices, intend to eat healthier foods, but commonly suffer from obesity. With obesity rates continuing to rise, public policy makers are attempting to help consumers battle this disease. Accordingly, the Affordable Care Act menu labeling provision was passed in the United States, and requires restaurants to include calorie labeling on their menus. The literature on the effectiveness of menu calorie labeling has yielded mixed results thus far. We propose that is because the initiative helps certain individuals, but not others. Since individuals do not often accurately self-report their attention to menu calorie labeling due to social desirability bias, we utilize an eye-tracking methodology that focuses on the time consumers spent looking at menu calorie information. This (attention) measure is seen as a mediating process by which restrained eating reduces caloric intake intentions. Our results point to menu calorie labeling being effective for restrained eaters, a group in need of assistance.